Photocurrent spectroscopy applied to thin film solar cells based on hydrogenated amorphous silicon (a-Si:H) - Valera Palacios, Aníbal (2005)
Using photocurrent spectroscopy, we report measurements of the photo responde below the optical gap in hydrogenated amorphous silicon (a-Si:H). The a-Si:H films were grown in a non conventional DC plasma assited discharge chamber. The measurements suggest that the density of states of this material is not very different than conventional intrinsic a-Si:H (device-quality) and not so extended as usually taken. The positions of the corresponding photovoltaic transition energies are determined and agree very well with known data obtained by other methods.